Stellarlune - Messenger, Shannon (Messenger, Shannon. Keeper of the lost cities, 2022)
Sophie Foster and her friends are divided, and Black Swan is desperate for Sophie's help with their own projects. But her instincts are leading her in a different direction, and she is starting to believe that Stellarlune and the mysterious Elysian might be the key to stopping the Neverseen. Every step that Sophie and her allies take sets them on course to a final confrontation with the Neverseen that will change the Lost Cities forever.